40‐GB/s all‐optical 3R regeneration based on AFL and SOA‐DI. Issue 2 (February 2016) - Chen, Xin; Lou, Caiyun; Zhao, Xiaofan; Huo, Li; Sun, Yu; Zhao, Lingjuan
ABSTRACT: In this article, 40‐Gb/s all‐optical 3R regeneration with a monolithic amplified feedback laser (AFL) as the all‐optical clock recovery and a semiconductor optical amplifier delayed interferometer (SOA‐DI) as the optical decision gate has been experimentally demonstrated. A 40‐GHz optical clock with low timing jitter and uniform amplitude was successfully recovered from the polarization mode dispersion (PMD) and noise degraded signal by the AFL. The PMD degraded signal was restored by the 3R regenerator with the Q‐factor and the amplitude uniformity improved. Bit‐error rate improvement of the noise degraded signal has also been achieved using the 3R regenerator. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:433–436, 2016